IMPLEMENTASI MANAJEMEN PERAWATAN LUKA KANKER BERBASIS MOBILE APP: LITERATUR REVIEW - Mustafidz, Mustafidz; Sukihananto, Sukihananto (Alauddin Scientific Journal of Nursing, 2023)
Background: Cancer wounds are one of the problems in cancer. Cancer wounds are included in chronic wounds where there is a failure or inhibiting factor in the wound healing process. Cancer wound care requires special competence. Characteristics of cancer wounds, such as pain, easy bleeding, and the amount of exudate, make nurses have to be maximal in providing cancer wound care. The field of information technology has begun to develop applications for chronic wound care to make wound care more effective and efficient. Objective: To see the implementation of the use of mobile apps in the field of wound care. Method: A literature review is the method used in this article. Literature was obtained from an online database and sorted using the prisma method. Results: The researcher analyzed 12 articles on wound care applications. Conclusion: The use of wound care applications can streamline the time and documentation of nursing care. Recommendation: Indonesia Nursing National Associations can develop wound care applications so they can be used by wound nurse practitioners in Indonesia. Keywords: chronic wound, luka kanker, malignant wound, mobile application, perawatan luka